ANALYSIS OF PROFIT MARGIN IN MURABAHAH FINANCING AT BMT FAUZAN AZHIIMA, PAREPARE CITY - S, Mirna; Damirah; Purnamasari, Rini (Islamic Financial And Accounting Review, 2023)
This study aims to determine the form of a murabahah financing contract at BMT Fauzan Azhiima Parepare city, determining the profit margin on murabahah financing and calculating the profit margin on murabahah financing at BMT Fauzan Azhiima Parepare city. This research is a quantitative descriptive model with case studies. This research describes the form of a murabahah contract , determining the margin of a murabahah contract and calculating the financing of a murabahah contract in 2015, 2016, 2017, 2018, 2019 and 2020 The results of this study indicate that (1) The form of the murabahah contract at BMT Fauzan Azhiima, Parepare City uses predetermined stages (2) Determination of the profit margin is seen from the financing proposed by the customer and the result of the agreement between the customer and BMT Fauzan Azhiima, Parepare City. (3) The calculation of the profit margin on murabahah financing illustrates the condition of the BMT when measured by the net profit margin ratio, which has fluctuated , namely in 2015 in very good condition, in 2016 in very good condition, in 2017 in very poor condition, in 2018 in the situation is very lacking, in 2019 it is sufficient, and in 2020 it is in very good condition.